The Evaluation of Enriched Theistic Centred Curriculum in Sekolah Dian Harapan and Sekolah Lentera Harapan, Indonesia - Romandito, Mahendrayudha (2022)
The Indonesian national 2013 kurikulum (K13) draws from the national ideology of Pancasila. There are five principles in Pancasila. The first one is the theistic principle relating to God-centred education emphasising faith and piety. It accommodates diversity in religions. The research was conducted to evaluate the implementation of the theistic principle in Sekolah Dian Harapan and Sekolah Lentera Harapan, as a Christian school system under a head office collectively known as SDLH. Both schools used enriched K13. The evaluation of curriculum implementation was done using Stufflebeam’s Context, Input, Process and Product evaluation model. The study employed qualitative methodology. It addressed both the macro and micro perspectives by looking at the whole school system as a single case, while treating each CIPP stage as a distinct unit of analysis. The data were collected through observations, interviews, and participatory self-studies. The respondents were the leadership team of 39 schools which consists of principals, vice-principals, and curriculum-coordinators. The findings show that God-centred education occurred intentionally in the SDLH school system. Nevertheless, this study found substantial shortcomings in the alignment of the implementation of the theistic Pancasilaist Godcentred education from Input to product of learning. While SDLH intended to convey GCE at the contextual level, the implementation was not deeply and profoundly effective. The inconsistency started at the input stage resulting in a weak learning process that affected the GCE delivery as reflected well in the product of learning. The research makes significant contributions to the theistic God-centred education in Indonesia in a way it highlights the crucial gaps which will help enable constructive curriculum alignment from policy to practice.